Kolaborasi Antar Pemangku Kepentingan dalam Pengembangan Urban Farming di Surabaya - Kurnia Sri Dewi; Yusuf Hariyoko; Hasan Ismail (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study explores the stakeholder synergy in the development of urban farming programs in Surabaya. Using qualitative descriptive methods, data was collected through interviews, documentation, and observation involving the DKPP, agricultural extension officers, farmer groups, and the local community. The findings indicate that strong commitment, competence, awareness, and continuity are the driving factors behind successful urban farming implementation. However, challenges such as declining active farmer groups and limited facilities must be addressed. This research contributes to the understanding of sustainable food security policies in urban settings.